Associations Between Ozone and Preterm Birth in Women Who Develop Gestational Diabetes. Issue 4 (3rd February 2015) - Lin, Yu-Ting; Jung, Chau-Ren; Lee, Yungling Leo; Hwang, Bing-Fang
Abstract: Prenatal exposure to ambient air pollutants might cause adverse birth outcomes; however, there have been few studies in which the association between air pollution and preterm birth was examined after stratifying by pregnancy complications. We conducted a population-based case-control study of 1, 510, 064 singleton births from the Taiwanese birth registry during 2001–2007. Of the total of 1, 510, 064 births, we designated all 86, 224 preterm births as the case group and then randomly selected an additional 344, 896 from the remaining births (equivalent to 4 full-term births for every 1 preterm birth) as the control sample. We used an inverse distance weighting approach to calculate an average exposure parameter for air pollutants. The adjusted odds ratio for preterm birth per 10-ppb increase in ozone was 1.12 (95% confidence interval: 1.01, 1.23) for women with gestational diabetes mellitus who were exposed in the third trimester and 1.02 (95% confidence interval: 1.01, 1.03) for women without gestational diabetes ( P for interaction <0.001). These findings suggest that exposure to ozone in pregnancy is associated with an increased risk of preterm birth, particularly for women who have gestational diabetes mellitus.